1996
DOI: 10.1210/jcem.81.11.8923829
|View full text |Cite
|
Sign up to set email alerts
|

Serum leptin levels in women with anorexia nervosa.

Abstract: Leptin is a protein encoded by the ob gene that is expressed in adipocytes and regulates eating behavior via central neuroendocrine mechanisms. Serum leptin levels have been shown to correlate with weight and percent body fat in normal and obese individuals; however, it is not known whether the regulation of leptin is normal below a critical threshold of body fat in chronic undernutrition. We investigated serum leptin levels in 22 women, aged 23 +/- 4 yr, with anorexia nervosa. Duration of disease, weight, BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
159
0
2

Year Published

1997
1997
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(176 citation statements)
references
References 13 publications
15
159
0
2
Order By: Relevance
“…Control subjects had leptin concentraLeptin and growth hormone de®ciency N Ozbey et al tions similar to those previously reported in healthy controls. 5,33,38 Our results might indicate increased production of leptin by per unit fat mass in GH de®ciency similar to the reported increase in ob messenger RNA content of adipocytes in obese humans. 5 Previous studies showed different results regarding leptin concentrations in GH de®ciency.…”
Section: Discussionsupporting
confidence: 86%
“…Control subjects had leptin concentraLeptin and growth hormone de®ciency N Ozbey et al tions similar to those previously reported in healthy controls. 5,33,38 Our results might indicate increased production of leptin by per unit fat mass in GH de®ciency similar to the reported increase in ob messenger RNA content of adipocytes in obese humans. 5 Previous studies showed different results regarding leptin concentrations in GH de®ciency.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, plasma leptin concentrations are significantly lower in patients with anorexia nervosa relative to those in healthy subjects (7). All of these findings are consistent with the notion that leptin reflects the total body fat content, thereby, suggesting that leptin may serve as a useful chemical marker of adiposity.…”
supporting
confidence: 80%
“…13,14 The relationship between adiposity and plasma leptin concentration seems to be independent of the level of exercise (our data, 13,15,16 ) and is true in extremes of nutritional status such as anorexia nervosa. 17 Furthermore, hormones other than leptin also respond to energy de®cit. For example, insulin decreases and cortisol increases in response to fasting, and both of these hormones are thought to regulate leptin expression/secretion.…”
Section: Discussionmentioning
confidence: 99%